2009
DOI: 10.1016/j.thromres.2009.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Role of the syncytium in placenta-mediated complications of preeclampsia

Abstract: The syncytiotrophoblast (SCT) is the outer layer of placenta which is in direct contact with maternal blood. As such it is uniquely positioned to alter maternal hemostasis and endothelial function. The syncytium is known to release anti-angiogenic factors including fms-like tyrosine kinase-1 (sFlt-1) and soluble endoglin (sEng), as well as the anti-fibinolytic factor plasminogen activator inhibitor-1 (PAI-1). Its release of microparticles has also been suggested to play a role in regulating maternal endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(36 citation statements)
references
References 58 publications
1
34
0
1
Order By: Relevance
“…The affected chorionic villi in our study also showed more roughened fibrillar skeleton with increased fibrin deposition (Figure 21). The same results were reported by Guller Seth [20] and Salafia et al [25] who revealed that there were aberrantly high levels of intervillous fibrin which is a critical component of physiological repair and differentiation of the placental villi [26].…”
Section: Disscussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The affected chorionic villi in our study also showed more roughened fibrillar skeleton with increased fibrin deposition (Figure 21). The same results were reported by Guller Seth [20] and Salafia et al [25] who revealed that there were aberrantly high levels of intervillous fibrin which is a critical component of physiological repair and differentiation of the placental villi [26].…”
Section: Disscussionsupporting
confidence: 75%
“…Our results were in harmony with Zhang et al [24] who performed a placental examination for changes with preeclampsia, and reported poor correlation between these changes with the clinical manifestations of pregnancy induced hypertension. The histological changes and clinical manifestation were also reported in a review article by Guller Seth [20] who explained how hypoxia/ reperfusion injury disrupts the syncytial architecture and results in the previously mentioned changes. The affected chorionic villi in our study also showed more roughened fibrillar skeleton with increased fibrin deposition (Figure 21).…”
Section: Disscussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Microvesicles' secretion in the placenta occurs both by blebbing ⁄ shedding of syncytiotrophoblast microparticles (STBM) from the plasma membrane [12][13][14] and by exosome release through the endosomal pathway. [1][2][3][4][5][6] STBM are 0.2-2 lm in size and are present in a low plasma concentration in normal pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced shedding of STBM promotes endothelial and immune cell dysfunction, inflammation and necrosis ⁄ apoptosis and is somehow associated with the placental pathophysiology in preeclampsia. [12][13][14] Distinguishing between STBM and exosomes as separate bioactive entities is required to determine precisely their role in reproduction. In this review, we will focus on the placenta-derived exosomes and discuss their role in normal pregnancy.…”
Section: Introductionmentioning
confidence: 99%